UNA ESCRITURA PROPIA. ANOTACIONES SOBRE LITERATURA MARGINAL EN BRASIL. - Serrano, Mary Luz Estupiñán (Revista Chilena de Literatura)
In this essay, we present the discussions related to the so-called marginal literature, a concept forged within the contemporary literary scene in Brazil, in which Ferréz's work has been especially celebrated since 2000. In order to do this, we first review different references and uses given to the term marginal throughout the Brazilian literary history in the 20th century. We then analyze the conditions that generated the contemporary definition of "marginal literature" and, thus, raise some questions about this idea in the field of literary and cultural criticism.